Revisiting the concept of CNS immune privilege - Louveau, Antoine (Trends Immunol, 2015)
Whereas the study of the interactions between the immune system and the central nervous system (CNS) has often focused on pathological conditions, the importance of neuroimmune communication in CNS homeostasis and function has become clear over that last two decades. Here we discuss the progression of our understanding of the interaction between the peripheral immune system and the CNS. We examine the notion of immune privilege of the CNS in light of both earlier findings and recent studies revealing a functional meningeal lymphatic system that drains cerebrospinal fluid (CSF) to the deep cervical lymph nodes, and consider the implications of a revised perspective on the immune privilege of the CNS on the etiology and pathology of different neurological disorders.